Food Safety, Market Organization, Trade and Development - Hammoudi, A (Springer, 2015)
This book provides an economic perspective on the effects of food safety standards on international trade. Focusing on food safety regulation at an international level and private food safety standards, the authors use contemporary methodologies to analyze supply chain structures and organization as well as food-chain actors’ strategies. They also evaluate the effects of these on both consumer health and developing countries’ access to international markets. The book provides ideas, suggestions and policy recommendations for reconciling economic interests with consumer health, which will be of special interest to academics as well as to practitioners.